Hyflex Project-based Learning and Students' High Order Thinking Skills: Its Impact and Relevance - Rochmahwati, Pryla; Syah, Nur Aini; Makmun, Nadiah (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2024)
Studies on project-based learning advocate the importance of cultivating high order thinking skills yet, little attention was paid to its implementation in the hybrid learning environment. This study aims to investigate the impact of blended project-based learning on critical thinking skills for students with different motivation level in the Academic writing course at IAIN Ponorogo. Using a Single Group of quasy-experimental design, this study investigated the impact of hyflex project-based learning in improving high order thinking skills within 30 students enrolled in an Academic Writing course. The study revealed considerable evidence that hyflex project-based learning is effective for improving students’ HOTs. Educators are recommended to embrace this hyflex and project-based learning into their curricula to harness the benefits of this innovative learning model.